Does Incubation Enhance Problem Solving? A Meta-Analytic Review [article]. - Sio, Ut Na
A meta-analytic review of imperical stdies that have investigated incubation effects on problem solving is reported. Although some researchers have reported increased solution rates after the incubation period (i, e., a period of time in which a problem is set aside prior to further attempts to solve), others have failed to find effects. The analysis examined the contributions of moderators such as problem type, presence of solution-relevant or misleading cues, and lengths preparation and incubation periods to incubation effects sizes. The authors identified a positive incubation effect, with divergent thinking tasks benefiting more than linguistic and visual insight tasks from incubation.Longer preparation periods gave a greater incubation effect, whereas filling an incubation period with a high cognitive demand tasks gave a smaller incubation effect. Surprisingly, low cognitive demand tasks yielded a stronger incubation effect than did rest during an incubation period when solving linguistic insight prolems. The existence of multiple types of incubation effect provide evidence for differential invocation of knowledge-based vs. strategic solution processes across different classes of problem, and it suggests that the conditions under which incubation can be used as a practical technique for enhancing problem solving must be designed with care. -- (from the author)